Current Panorama and Challenges in Preventing Ankle Injuries in Athletes - Azzini, Vitor Ohana Marques; Lopes, Cristianne Confessor Castilho; Beker, Natascha Szumsztajn; Guimarães, Larissa Silva; Furlan, Daniel; Lopes, Lucas Castilho; Filho, Mushue Dayan Hampel Vieira; Lopes, Maria Eduarda Castilho; Lopes, Eduardo Barbosa; Pitanga, Fábio Herget; Guilherme David Packer Rodrigues (International Journal of Medical Science and Clinical Research Studies, 2024)
Introduction: The review addresses ankle injuries in athletes, highlighting their prevalence and impact on sports performance. Injuries, such as sprains and fractures, result from a variety of factors, including direct trauma and sudden movements. Prevention is crucial and involves specific training, use of appropriate equipment and innovative strategies. Objective: Check current challenges in preventing ankle injuries in athletes. Methods: This study constitutes a systematic review, classified as exploratory and descriptive. The preparation of the research was a bibliographical search in electronic databases on methods associated with RSL (Systematic Literature Review) and the applications of SMARTER (Simple Multi-Attribute Rating Technique using Exploiting Rankings). The study methodology is a systematic, exploratory and descriptive review, using qualitative and quantitative methods. The bibliographic search covered several databases, with well-defined inclusion and exclusion criteria. Data analysis was conducted by three independent researchers. Results and Discussion: The results revealed 399 articles, 11 of which were included in the review. Various studies addressed diagnostic, preventive and therapeutic methods. Interventions such as weight-bearing MRI, neuromuscular training programs, low-friction adhesives and proprioceptive training stand out. The understanding of radiographic patterns and the analysis of innovative techniques, which enrich the preventive approach. Conclusion: The conclusion highlights important insights, highlighting the need for more comprehensive research, standardization and long-term studies. Despite limitations, promising advances indicate a positive shift in ankle injury prevention, requiring a collaborative approach between researchers, healthcare professionals and athletes.